2021
DOI: 10.1107/s2056989021005491
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and Hirshfeld surface analysis of 1-[(E)-2-(5-chloro-2-hydroxyphenyl)hydrazin-1-ylidene]naphthalen-2(1H)-one

Abstract: The title compound, C16H11ClN2O2, was obtained by diazotization of 2-amino-4-chlorophenol followed by a coupling reaction with β-naphthol. There are two molecules (A and B) in the asymmetric unit. The crystal structure features only one type of intermolecular interaction, that is strong hydrogen bonds involving the hydroxyl group. The naphthol and phenol fragments attached to the C=N—N— moiety exhibit an s-trans conformation. In addition, those fragments are almost coplanar, subtending a dihedral angle of 13.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In both methods, the molecule is Z-isomer with quite planar and the most important deviation is observed for the carbon C18:0,141Å, the rings of benzene and naphtol are in the (E) position with the -N=N-bond, the same configuration is observed for same compounds [38,39]. Moreover, all the angles and bond lengths of benzene and naphthol are in their expected ranges [40][41][42].…”
Section: Xrd-crystal and Dft-optimization Analysismentioning
confidence: 73%
“…In both methods, the molecule is Z-isomer with quite planar and the most important deviation is observed for the carbon C18:0,141Å, the rings of benzene and naphtol are in the (E) position with the -N=N-bond, the same configuration is observed for same compounds [38,39]. Moreover, all the angles and bond lengths of benzene and naphthol are in their expected ranges [40][41][42].…”
Section: Xrd-crystal and Dft-optimization Analysismentioning
confidence: 73%
“…The N19-N20 [1.310 (2) A ˚] and C8-O17 [1.264 (3) A ˚] bond lengths indicate that the compound adopts the neutral hydrazo tautomer form upon crystallization. This is common when an OH group is in the ortho-position relative to the azo group, leading to a proton being transferred from the naphthol group to the azo group (Benaouida et al, 2023;Bougueria et al, 2021). The internal alternate angles at N19 and N20 are identical within experimental error with an average value of 118.25 (2) � .…”
Section: Structural Commentarymentioning
confidence: 88%
“…A search of the Cambridge Structural Database (CSD; Version 2023.2.0, last update September 2023; Groom et al, 2016) for 1-phenylazo-2-naphthol derivatives revealed that numerous azo-2-naphthol compounds with similar structures have been synthesized using various aromatic primary amines. Benosmane et al, 2013), 1-[(E)-2-(5-chloro-2 hydroxyphenyl) hydrazin-1-ylidene]naphthalen-2(1H)-one (UVIDOV; Bougueria et al, 2021), OGUXAP01, OGUXAP02 and OGUXAP03;Gilli et al, 2002), (E)-1-[2-(3-nitrophenyl)hydrazinylidene]naphthalen-2(1H)-one (FIFCEG; Benaouida et al, 2023), 1-(phenylazo)-2-naphthol (JARPEX; Olivieri et al, 2002), (Z)-1-(2-phenyldiazen-2-ium-1-yl)naphthalen-2-olate (TIFTEJ01; Benosmane et al, 2015). All these compounds belong to the azo dyes family and share a common base structure -a benzene ring and a naphthalene ring system linked with an oxygen in the ortho position relative to the azo group.…”
Section: Database Surveymentioning
confidence: 99%
“…A search for 1-phenylazo-2-naphthol derivatives in the Cambridge Structural Database (CSD; Version 2022.3.0, last update November 2022; Groom et al, 2016), revealed several examples of structurally similar azo-2-naphthol compounds prepared using different aromatic primary amines. The crystal structures of 1-[(E)-2-(5-chloro-2 hydroxyphenyl)hydrazin-1ylidene]naphthalen-2(1H)-one (Bougueria et al, 2021), (4-aminosulfonylphenyl)[(2-oxidonaphthalen-1-yl)-imino]azanium (Benosmane et al, 2016), (E)-1-(4-fluorophenyl)-2-(2-oxidonaphthalen-1-yl)diazen-1-ium (Bougueria et al, 2017) have been reported, as well as the structural and optoelec- tronic properties and theoretical investigation of a novel square-planar nickel (II) complex with an (o-tolyldiazenyl) naphthalen-2-ol ligand (Benosmane et al, 2023) that exhibits structural diversity with interesting optoelectronic properties.…”
Section: Database Surveymentioning
confidence: 99%